State aid and competitiveness of the hard coal mining industry in the European Union - Izabela Jonek-Kowalska (Institute of Economic Research (IER), 2014)
The hard coal mining industry in the European Union (EU) is in decline, mostly due to a lack of price competitiveness. It is maintained, to a great extent, by state aid; a key objective of the industry's existence is to provide energy security and guarantee employment in the mining regions. In Poland, the hard coal mining industry is currently undergoing a serious crisis that threatens the two largest mining enterprises with bankruptcy. In addition, due to the European Union's restrictions concerning the circumstances of granting state aid, these enterprises cannot count on the financial support for the repair restructuring that they used on a large scale until 2011. Therefore, in this article, the main objective is to determine the influence of state aid on the competitiveness of the hard coal mining industry in 12 countries of the EU, including Poland in specific. In order to achieve the stated objective, the article is divided into three parts. The first part consists of a literature review and legal regulations that are related to state aid for the hard coal mining industry in the EU are presented. The second part identifies the amount of state aid for the mining industry in the examined countries. Next, the influence of the state aid on the economic-financial conditions and competitiveness of the industry in the examined countries is examined. The third assesses the financial results of 24 Polish hard coal mines. The data of Eurostat and EURACOAL were used in the research. Furthermore, the primary data from the Polish mines of power hard coal were also used. The research methodology includes the indicators from the area of effectiveness and productivity assessment, as well as production quality assessment in the mining industry. The research results make it possible to extend knowledge in the range of the influence of the state on the competitiveness of the traditional industries and their restructuring.
Keywords: D22; E65; F30; F60; 330; state aid; competitiveness of industries; hard coal mining industry in Poland and the EU; Polish mining enterprises